Management of immigration and pregnancy screening in northeastern Italy. - Tamaro, Giorgio; Parco, Sergio (Risk Manag Healthc Policy, 2011)
This study assesses the impact of immigration in Friuli Venezia Giulia, a region of northeastern Italy, on the epidemiological features of hemoglobin patterns and on prothrombotic and trisomy risk in pregnancy for patients of non-Italian origin. This study follows a series of studies on the incidence of thalassemia and other hemoglobinopathies with reduced globin chain synthesis, that were performed during the postwar (1939-45) period in Friuli Venezia Giulia following immigration into the region from Istria and Sardinia (regions of northern and central Italy). Current data show that today's constantly growing immigration into the region differs from previous decades, in terms of origin and quantity of migrants, who mainly come from third world countries. This has a significant impact on health care issues, and more specifically on prospective health screening for foreigners. The authors conclude that scholastic education and hospital services, either public or private, and voluntary associations, may contribute to solving the problem, but only in terms of training and organization, for non-European Union citizens arriving in northern Italy and neighboring areas, especially those from Africa, Asia, Latin America, and eastern Europe.